Technology Resources for Teaching Secondary Mathematics: Lessons from Early and Late Adopters of Technology in Kenya - Kamau, Leonard M.; Mwania, Jonathan; Njue, Antony K. (Asian Journal of Contemporary Education, 2018)
This study investigated the extent to which access to technology resources influenced their adoption by mathematics teachers in their teaching. The study conducted in Nairobi County in the summer of 2013 applied Rogers’ diffusion of innovation theory. Participants were categorized either as early or later adopters of technology based on availability of technology or whether or not they had adopted technology for instructional purposes at their schools. Six teachers were selected; three in each category for interviews and classroom observations. The findings revealed that early adoption of technology was associated with the teachers (early adopters) belief that technology would benefit them and their students. Late adopters on their part tended to believe that technology was not compatible with their instructional needs. Interestingly, both categories of adopters agreed that technology was complex to use for instructional purposes pointing towards lack of adequate training. Similarly, both groups considered computer department in their schools a hindrance to technology adoption. Findings also highlighted the scarcity of technology resources which impacted negatively on the process of adoption. These findings suggest that teachers be trained adequately and role of the computer department as the custodian of technology at schools be liberalized. Additionally, stakeholders are advised to consider installing technology resources in classes to encourage their use rather than locking them in laboratories.